Answer:
x = {π/4, 7π/6, 5π/4, 11π/6} +2kπ . . . for any integer k
Explanation:
![\frac{\sin^3{x}}{1+cos(x)}+\frac{\cos^3{x}}{1+sin(x)}=cos(2x)+2cos(x)-1\\\\\frac{sin(x)(1-\cos^2{x})}{1+cos(x)}+\frac{cos(x)(1-\sin^2{x})}{1+sin(x)}=\cos^2{x}-\sin^2{x}+2cos(x)-1\\\\sin(x)(1-cos(x))+cos(x)(1-sin(x))=\cos^2{x}-\sin^2{x}+2cos(x)-1\\\\sin(x)+cos(x)-2sin(x)cos(x)=2cos(x)-2\sin^2{x}\qquad\text{use $1=s^2+c^2$}\\\\sin(x)+2\sin^2{x}-cos(x)-2sin(x)cos(x)=0\\\\sin(x)(1+2sin(x))-cos(x)(1+2sin(x))=0\\\\(sin(x)-cos(x))(1+2sin(x))=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/ti701a2y0z14kwhamsnf6ps924a191ng4z.png)
This will have solutions where the factors are zero.
sin(x) -cos(x) = 0
Dividing by cos(x), we have ...
tan(x) -1 = 0
x = arctan(1) = π/4, 5π/4
1 +2sin(x) = 0
sin(x) = -1/2
x = arcsin(-1/2) = 7π/6, 11π/6
The four solutions in the interval [0, 2π] are x = {π/4, 7π/6, 5π/4, 11π/6}. Solutions repeat every 2π radians.
_____
Additional comment
We have made use of the factoring of the difference of squares:
(1 -a^2) = (1 -a)(1 +a)
and we have made use of the cosine double angle identity:
cos(2x) = cos(x)^2 -sin(x)^2
The "Pythagorean" identity for sine and cosine was used several times:
1 = sin(x)^2 +cos(x)^2